Parandrinae from Cuba (Coleoptera, Cerambycidae) - Deler-Hernández, Albert; Santos-Silva, Antonio (Papéis Avulsos de Zoologia, 2011)
Three species of Parandrinae are recognized from Cuba, all belong to Birandra (Yvesandra) Santos-Silva & Shute, 2009: B. (Y.) cubaecola (Chevrolat, 1862); B. (Y.) cribrata (Thomson, 1861); and B. (Y.) latreillei Santos-Silva & Shute, 2009. The latter, confused with the former by Zayas (1957, 1975) is confirmed as a common species on the island. Birandra (Y.) cubaecola is excluded from the fauna of Puerto Rico; B. (Y.) cribrata is also excluded from Puerto Rico as well as Hispaniola.